On the evolution of artificially maturated hydrocarbon source rocks - de Lacerda, D. L. P.; Morschbacher, M. J.; Justen, J. C. R.; Vasquez, G. F.; Spigolon, A. L. D.; Menezes, T. R.; Skinner, R. (Frontiers in Earth Science, 2023)
The elastic moduli are a function of properties that could vary between samples and change during maturation. Consequently, the effects of organic matter maturation on the elastic wave velocities of organic-rich rocks are challenging to describe. This work analyzes the isolated maturation effects on the organic content, pore volume, microstructure, and propagation velocities of elastic waves. To avoid any initial rock heterogeneity, we prepared a series of homogeneous samples from a unique outcrop block collected on the Eagle Ford formation with mineral composition initially determined using X-ray diffraction. From the initial set, four samples were held in their original condition and four were artificially maturated by hydropyrolysis until transformation rates were up to 95%. Then, the evolution of the sample properties was examined using an association of LECO TOC, Rock-Eval pyrolysis, vitrinite reflectance, mercury intrusion porosimetry (MIP), and ultrasonic pulse propagation. In addition, scanning electron microscopy images registered the microstructure evolution. To evaluate the effects of maturation on pore geometry and the organic matter elastic moduli, we analyze the relationship between the measured quantities using a rock physics inclusion model with the unmeasured properties taken as fitting parameters. The hydropyrolysis maturation increases the vitrinite reflectance from the initial 0.55% to 1.34% on the most matured sample. A total organic carbon reduction from 4.2% to 2.1% and a porosity increase from 9.2% to 21% are associated with observed maturation. The geochemical characterization on cleaned samples reveals an initial increment of soluble organic matter followed by a monotonical reduction related to oil migration out of bulk volume. The measurement of wave propagation velocities as a function of confining pressure displays an increasing pressure sensitivity with a downward trend in both velocity moduli. The petrophysical analysis indicates that the porosity increases through organic matter consumption and pore creation. The rock physics diagnoses indicate a decrease in the pore aspect ratio with an increase in the elastic modulus of the organic matter with maturation.